THE IMPACT OF ROLE OVERLOAD ON JOB STRESS AND EMPLOYEE JOB SATISFACTION: A STUDY ON EMPLOYEES IN THE OIL REFINERY SECTOR OF ASSAM (CAHIERS MAGELLANES-NS, 2024)
The study examines the intricate connection between workplace stress, role overload, and job satisfaction among employees of oil refineries in Assam. The challenging nature of refinery operations, along with a high-risk environment, significantly contributes to occupational stress, leading to decreased job satisfaction. A structured questionnaire was administered to gather data from 224 executive personnel working in the four oil refineries in Assam. The data was then analysed to assess the impact of workload on employee stress and job satisfaction. The data reveals a strong connection between having too many responsibilities at work and experiencing job-related stress, which ultimately results in lower job satisfaction. The study underscores the significance of implementing effective stress management techniques and organizational interventions to decrease role overload and enhance job satisfaction among employees at the oil refineries in Assam. The study also explores the implications for management practices and policy recommendations aimed at creating a healthier and more productive work environment.